Numerical explorations of the Ngai-Pissarides model of growth and structural change - Andreas Dietrich; Jens J. Krüger (Technische Universität Darmstadt, Department of Law and Economics, 2010)
In this paper we specialize the Ngai-Pissarides model of growth and structural change [American Economic Review 97 (2007), 429-443] to the case of three sectors, representing the primary (agriculture, mining), secondary (construction, manufacturing) and tertiary (services) sectors. On that basis we explore the dynamic properties of the model along the transition path to the steady-state equilibrium by numerical methods. Our explorations show that the model misses several stylized facts of structural change among these sectors. We propose several extensions of the model to align the model more closely with the facts.
Keywords: L16; O14; O41; 330; economic growth; structural change; transition path